Alkenylphenols from Piper dilatatum and P. diospyrifolium. (June 2018) - Yoshida, Nídia C.; Benedetti, Aline M.; dos Santos, Ruilan A.; Ramos, Clécio S.; Batista, Ronan; Yamaguchi, Lydia F.; Kato, Massuo J.
Graphical abstract: Highlights: Three new alkenylphenols were isolated from Piper species. An unusual alkenylphenol bearing two double bonds is described. Structure elucidation was carried out by analysis of 1D and 2D NMR and MS data. Abstract: As part of our continuing phytochemical survey on Piper species, three previously undescribed alkenylphenols were isolated and characterized, including 4-[(3′ E )-tetradec-3′-en-1-yl] phenol (1 ) and 4-[(2′ E, 4′ E )-heptadeca-2′, 4′-dien-1-yl] phenol (3 ) from P. diospyrifolium and 4-[(3′ E )-hexadec-3′-en-1-yl] phenol (2 ) from P. dilatatum . The structures of the compounds were determined based on spectroscopic analyses including 1D and 2D NMR and high-resolution mass spectrometry.